2006
DOI: 10.1109/tpwrs.2005.860931
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis Between Synchronous and Induction Machines for Distributed Generation Applications

Abstract: This paper presents a detailed comparative analysis between synchronous and induction machines for distributed generation applications. The impacts of these generators on the distribution network performance are determined and compared by using computational simulations. The technical factors analyzed are steady-state voltage profile, electrical power losses, voltage stability, transient stability, voltage sags during unbalanced faults, and short-circuit currents. The results showed that the best technical cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
20

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(85 citation statements)
references
References 12 publications
(22 reference statements)
0
65
0
20
Order By: Relevance
“…Voltage sag is not a complete interruption of power; it is a temporary drop below 90% of the nominal voltage level. Nowadays, Voltage sag is the most significant power quality (PQ) problem faced by industrial customers as well as large commercial customers [8]. Depending on the magnitude and duration of the voltage sag, the effect of sag varies on the sensitivity of the equipment.…”
Section: Inverter Based Dgmentioning
confidence: 99%
“…Voltage sag is not a complete interruption of power; it is a temporary drop below 90% of the nominal voltage level. Nowadays, Voltage sag is the most significant power quality (PQ) problem faced by industrial customers as well as large commercial customers [8]. Depending on the magnitude and duration of the voltage sag, the effect of sag varies on the sensitivity of the equipment.…”
Section: Inverter Based Dgmentioning
confidence: 99%
“…Thus we adopted here the block diagram shown in Figure 8 in order to assess the dynamic response of the system of Figure 12, towards the contingency to be applied. Similar works using ATP were developed like (Saldaña et al, 2006) and an important work about distributed generation can be found in through (Freitas et al 2006). …”
Section: Data Needed For G1 (G1 = G2)mentioning
confidence: 99%
“…A schematic diagram of the distribution system model [43] for bus 12 of the New England system is illustrated in Fig. 15.…”
Section: B Impact Of Wind Farm Locationmentioning
confidence: 99%